Comparison of different CNN architectures for brain tumor detection using fMRI - Mashiat, Afsara; Akhlaque, Reza Rifat; Fariha, Fahmeda Hasan; Patwary, Md Shawkat Hossain (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.